Internal Validity and Internal Validity Threats - Imas Siti Masuroh; Inda Dzil Mustaqim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
A study is said to be valid if it has a proven causal relationship between its variables. A study is said to have validity if it can minimize various confounding factors that can affect the results and the level of trust in the study. Several threats to internal validity that can affect the results of the study The purpose of this study is to describe the role of internal validity in a scientific study and the threats to internal validity. The articles used as sources of literature review in this study are based on Google Scholar and PubMed data. The search for research literature uses the keywords